Phytochemical Profiling and Evaluation of Cytotoxic Potential of Cucumis prophetarum L. Fruit Extract - Javed, Sadique Akhtar; Khalid, Asaad; Hassani, Rym; Mohan, Syam; Abdalla, Ashraf Nabiel; Rehman, Zia ur; Najmi, Asim; Zoghebi, Khalid; Makeen, Hafiz Antar; Albratty, Mohammed (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: The present study examined phytochemical composition of ethanolic extract and evaluated cytotoxic properties of Cucumis prophetarum L. Materials and Methods: Phytochemical composition of extract was evaluated by GC-MS and screened for cytotoxic activity by MTT assay. The human cancer cell-lines including MCF7, A2780, HT29, and Normal Fetal Lung Fibroblasts (MRC5), used to determine cytotoxicity and selectivity index of the extract. Results and Discussion: Fatty acid esters (43.74%), phthalic acid diesters (11.38%), fatty acid silyl esters (4.15%), and siloxane derivatives (3.88%), aromatic monoterpenes (2.75%) and pentacyclic triterpenoids (1.21%) were the main constituents detected in the extract. Results indicated that MCF7 cells exhibited highest sensitivity (IC50: 3.30 μg/mL) and the extract was selective and caused early apoptosis against the same cell-lines. Conclusion: The outcomes of this investigation indicated that the bioactive components in the extract might be employed for cytotoxic purposes. The study will be useful to establish the scientific basis for ethnopharmacological usage of the tested plant.
Keywords: Cucumis prophetarum L; GC-MS; Phytochemical; Cytotoxic; Selectivity index; Apoptosis